2004
DOI: 10.4315/0362-028x-67.9.1933
|View full text |Cite
|
Sign up to set email alerts
|

Validated Sandwich Enzyme-Linked Immunosorbent Assay for Casein and Its Application to Retail and Milk-Allergic Complaint Foods

Abstract: Cows' milk is a commonly allergenic food. Cross-contamination of milk proteins into nondairy, kosher-pareve foods prepared on shared processing equipment can cause severe, life-threatening reactions in milk-allergic individuals. A sandwich-type enzyme-linked immunosorbent assay (ELISA; 96-well plate format) was developed for the detection of undeclared casein in foods. Rabbit anti-casein antibodies were used as the capture reagent. Food samples and standards were ground, extracted in 0.01 M phosphate-buffered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…European Legislation, such as Directive 2003/89/EC and amendments (European Commission, 2003) requires that all ingredients added to food products have to be labelled and demands the obligatory declaration of those liable to cause allergies or intolerances in which milk and egg and products thereof are included. Furthermore, the inadvertent presence of allergens results from practices in the food industry such as the use of contaminated raw materials, inadequate cleaning of shared equipment or other sources of cross-contact (Hefle & Lambrecht, 2004). Therefore, reliable detection methods for food allergens are necessary to ensure its compliance with the food labelling and to improve consumer protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…European Legislation, such as Directive 2003/89/EC and amendments (European Commission, 2003) requires that all ingredients added to food products have to be labelled and demands the obligatory declaration of those liable to cause allergies or intolerances in which milk and egg and products thereof are included. Furthermore, the inadvertent presence of allergens results from practices in the food industry such as the use of contaminated raw materials, inadequate cleaning of shared equipment or other sources of cross-contact (Hefle & Lambrecht, 2004). Therefore, reliable detection methods for food allergens are necessary to ensure its compliance with the food labelling and to improve consumer protection.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are mainly based on the interaction between the allergenic protein and the specific antibodies obtained against it. At present, only the ELISA technique is used in the routine analysis due to its high precision, simple handling and good potential for standardisation (de Luis, Pérez, Sánchez, Lavilla, & Calvo, 2007;Hefle & Lambrecht, 2004;Mariager, Solve, Eriksen, & Brogren, 1994;Poms et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hefle and Lambrecht (2004) when analysing non-milk contained foods found that all dark chocolate samples and 18% of sorbets, fruit juice bars and drinks samples analyzed contained undeclared casein.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the RIE method can be used to confirm the casein analyses from an indirect ELISA recently developed in our laboratory; with a LOD of B/1 mg kg (1 (Sletten et al unpublished data). A recently developed sandwich ELISA has also been described, with a claimed detection limit of 0.5 mg kg (1 (Hefle & Lambrecht 2004).…”
Section: Discussionmentioning
confidence: 99%